2016
DOI: 10.12659/msm.899980
|View full text |Cite
|
Sign up to set email alerts
|

Sam68 is Overexpressed in Epithelial Ovarian Cancer and Promotes Tumor Cell Proliferation

Abstract: BackgroundEpithelial ovarian cancer (EOC) is the deadliest gynecological malignancy, and evidence is accumulating on how molecular markers may be associated with the origin and process of EOC. Sam68 (Src-associated in mitosis, of 68 kD), is a K homology domain RNA-binding protein that has been investigated as a risk factor in multiple types of tumors. The aim of the present study was to investigate the contribution of the Sam68 gene in the pathogenesis of EOC.Material/MethodsWestern blot assay and real-time qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In ACTHomas, our results demonstrated that the altered expression of only two SFs, MAGOH and KHDRBS1, was sufficient to fully discriminate ACTHomas from NPs. These SFs were markedly upregulated in ACTHomas, which is in accordance with the increased expression of KHDRBS1 found in gastric cancer, epithelial ovarian cancer or sacral chordomas, wherein its presence was associated with poor prognosis and aggressive characteristics [65,66]. Likewise, MAGOH has been shown to be differentially expressed in breast cancer, where it served, together with other RNA processing factors, to develop a robust stratification of breast cancer subtypes [67].…”
Section: Discussionmentioning
confidence: 56%
“…In ACTHomas, our results demonstrated that the altered expression of only two SFs, MAGOH and KHDRBS1, was sufficient to fully discriminate ACTHomas from NPs. These SFs were markedly upregulated in ACTHomas, which is in accordance with the increased expression of KHDRBS1 found in gastric cancer, epithelial ovarian cancer or sacral chordomas, wherein its presence was associated with poor prognosis and aggressive characteristics [65,66]. Likewise, MAGOH has been shown to be differentially expressed in breast cancer, where it served, together with other RNA processing factors, to develop a robust stratification of breast cancer subtypes [67].…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, the production of IL-8 and G-CSF cytokines also confirmed that alginate particles can promote cytokine secretion ( Figure 5A, 5B ). These results indicated that alginate particles can serve as an adjuvant to treat tumors, not only for melanomas, but also other tumors such as ovarian cancers, for which several biomarkers have been recently found [ 18 23 ]. We only investigated macrophages in this study, but during the immune responses to vaccination, other cells, especially dendritic cells, B cells, and natural killer cells, also have important functions.…”
Section: Discussionmentioning
confidence: 99%